Reestructuración técnico administrativa en la empresa Box Servicios Ltda. (2019)
Box Servicios Ltda., Is a company that is dedicated to the manufacture of office furniture, with an experience in the market for approximately 17 years, however it has been presenting both technical and administrative difficulties, which reduce its profits. The presentation of the proposal seeks to provide solutions to both technical and administrative problems, through the standardization of processes and times, a new approach to plant design and additionally providing a future vision based on the fulfillment of objectives.